Catalyst for preparing benzene by dehydrogenation of cyclohexane as well as preparation method and application of catalyst

By using a catalyst composed of platinum, tin and alkali metal on the Ti-Si@Al2O3 support in the cyclohexane dehydrogenation process, the PtSn active center is formed and anchored on the Ti-Si@Al2O3 framework, the problems of by-product generation and catalyst deactivation under high temperature conditions are solved, and a highly efficient and energy-saving cyclohexane dehydrogenation and benzene production process is achieved.

CN119633814APending Publication Date: 2025-03-18GUIYAN IND CATALYST (YUNNAN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411861873.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the dehydrogenation process of cyclohexane, a variety of by-products will be generated under high temperature conditions, resulting in accelerated catalyst deactivation and increased the economic cost of industrial plants.

Method used

Through the synergistic action of the precious metal precursor-support-loading method, a catalyst composed of platinum, tin and alkali metal on the Ti-Si@Al2O3 support was prepared to form a PtSn active center, and was anchored on the Ti-Si@Al2O3 framework through the Ti-O bond to improve the stability and toxicity of the catalyst.

Benefits of technology

It achieves efficient dehydrogenation at a lower reaction temperature (265-275℃), and the cyclohexane conversion and benzene yield both reach more than 99.35%, effectively inhibiting side reactions, extending the service life of the catalyst, and reducing the cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633814A_ABST
    Figure CN119633814A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst for preparing benzene by dehydrogenation of cyclohexane as well as a preparation method and application of the catalyst. The catalyst takes Ti-Si-coated Al2O3 as a carrier, precious metal Pt as an active component, alkali metal and tin. The catalyst comprises, by mass, 0.3-1.5 wt% of platinum as an active component of the catalyst, 0.01-0.4 wt% of alkali metal as an active component of the catalyst, and 0.01-0.2 wt% of tin as an active component of the catalyst. The catalyst is high in benzene yield, good in toxicity resistance, high in regeneration activity and good in thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for preparing benzene by dehydrogenating cyclohexane, and a preparation method and application thereof, belonging to the technical field of catalyst preparation. Background Art

[0002] Cyclohexane is mainly derived from the production device of cyclohexanone by hydration, and its main production process is to produce cyclohexanone through the reaction of raw material benzene hydrogenation, cyclohexene hydration, cyclohexanol dehydrogenation, etc. In the production process of cyclohexanone by hydration, 20-25% of byproduct cyclohexane will be produced, so that the effective utilization rate of raw material benzene can only reach 75-80%. Through the production system of cyclohexane dehydrogenation to prepare benzene, the byproduct cyclohexane of the cyclohexanone device can be converted into benzene and hydrogen through dehydrogenation reaction, and then the benzene and hydrogen are recycled back to the cyclohexanone device as raw materials, so that the byproduct cyclohexane is effectively utilized, and the raw materials and products are closed-loop circulated in the device, achieving the purpose of green, environmental protection, high efficiency, energy saving, and no waste generation, while reducing the production and operation costs of the outsourcing of raw material benzene and the supporting hydrogen production device. CN 115445612A discloses a dehydrogenation catalyst, its preparation method and application, and a method for dehydrogenating cyclohexane to prepare benzene rings. The catalyst contains Pt, and the auxiliary agent contains Sn, alkali metals, rare earth metals Cu, Co, Zn, Ga, W, Re, etc. The preparation method of the catalyst is as follows: firstly, the active component is loaded on the alumina carrier, and then the active component metal oxide is reduced after the first calcination, and then the first metal auxiliary agent and the second metal auxiliary agent are loaded, and then the second calcination is performed. The active component metal oxide is first reduced to convert it into a metallic state, and then interacts with the auxiliary metal, and the active metal in the metallic state interacts strongly with the auxiliary metal, thereby showing a better synergistic effect. The active component is distributed in a shell layer on the carrier, thereby improving the utilization efficiency of the active metal. By converting the active metal into a metallic state and then acting on the auxiliary metal, the interaction force between the active metal and the auxiliary metal, especially the first auxiliary metal, is enhanced, and the auxiliary metal is prevented from being converted into a low-valent state or even a metallic state, so that the catalyst still has high activity and stability under the condition of a low active component content, and has the advantage of low cost. The catalyst is contacted with cyclohexane for reaction, the reaction temperature is 280°C-430°C, the reaction pressure is 10-800kPa, the cyclohexane conversion rate is more than 95%, and the benzene selectivity is more than 93%. The catalyst is reduced by multiple calcinations by step-by-step impregnation to improve the activity and stability of the catalyst. CN 115999591 A relates to an alumina carrier of sulfate radical and components with the following contents calculated on the basis of alumina: 0.05-3.0% by mass of group VIII metal, 0.05-3.0% by mass of group VIIB metal, 0.05-1.0% by mass of Tm or Sm, 0.1-3.0% by mass of halogen, and 0.5-1.5% by mass of sulfate radical. The catalyst is used for the dehydrogenation of hexacyclic alkane to produce aromatic hydrocarbons, and has high aromatic hydrocarbon selectivity, activity stability and good regeneration performance. CN 115999591A relates to a catalyst for the dehydrogenation of hexacyclic alkane to produce aromatic hydrocarbons and a preparation method thereof. The catalyst has a benzene yield of more than 97% at 480°C, 0.85MPa, feed mass space velocity of 4.0h-1, hydrogen / hydrocarbon volume ratio of 1000:1, and reaction time of 192 hours.CN 115703062A discloses a low-temperature dehydrogenation catalyst and a preparation method thereof. The dehydrogenation catalyst comprises an active component Pt, an auxiliary agent, chloride ions and a carrier. The cyclohexane conversion rate reaches 97% and the benzene selectivity reaches 100%.

[0003] However, in the cyclohexane dehydrogenation process, the higher reaction temperature is a difficulty in the comprehensive utilization of cyclohexane. The products of cyclohexane dehydrogenation are theoretically benzene and hydrogen, but in fact, the cyclohexane dehydrogenation reaction process under high temperature conditions not only generates benzene and hydrogen, but also generates ethylbenzene, toluene, n-heptane, methylcyclopentane, n-pentane, cyclopentane and more than a dozen by-products. The dehydrogenation process above 350°C may also generate more complex heavy components such as biphenyl. At the same time, after the catalyst reacts at high temperature for a long time, the catalyst deactivation rate accelerates, which will affect the life of the catalyst and lead to high economic cost of industrial equipment. Based on these problems, the present invention not only improves catalyst performance, selectivity, stability and regeneration performance, reduces reaction temperature, reduces by-products, but also reduces the amount of precious metals, reduces catalyst costs, and finally realizes energy-saving, environmentally friendly and efficient cyclohexane dehydrogenation benzene process, which has important practical significance. Summary of the invention

[0004] The object of the present invention is to provide a catalyst suitable for the production of benzene by dehydrogenation of cyclohexane, and a preparation method and application thereof. The catalyst has the characteristics of high effective utilization rate of unit active components, high benzene yield, good catalyst anti-toxicity, high catalyst regeneration activity, good thermal stability, low loss, low reaction temperature, etc. The catalyst has good regeneration and anti-toxicity while having a high yield, effectively prolonging the life of the catalyst and reducing the cost of using the catalyst, and reducing the amount of precious metals on the catalyst.

[0005] The invention provides a catalyst for preparing benzene by dehydrogenating cyclohexane. The catalyst takes Ti-Si@Al2O3 as a carrier, platinum, tin and alkali metals as active components. The content of platinum of the active component is 0.3-1.5wt% of the mass of the catalyst, preferably 0.3-1.0wt%, more preferably 0.3-0.8wt%; the content of alkali metal is 0.005-0.4wt% of the mass of the catalyst, and the content of tin is 0.01-0.2wt% of the mass of the catalyst. The Ti-Si@Al2O3 carrier comprises silicon oxide, titanium oxide and aluminum oxide. The titanium oxide accounts for 0.02-8% of the mass of the carrier, and the silicon oxide accounts for 0.1-15% of the mass of the carrier.

[0006] A preparation method of a catalyst for dehydrogenating cyclohexane to prepare benzene comprises the following steps: adding Sn metal salt, a platinum precursor compound M1Pt[O(SO)R1]X and an alkali metal chloride to an alcohol aqueous solution, adjusting the solution pH value to 1.0-2.5, wherein the molar ratio of the Sn metal salt, M1Pt[O(SO)R1]X and the alkali metal chloride is 0.5:2-7:1-10, to obtain an impregnation solution; impregnating the obtained impregnation solution onto a Ti-Si@Al2O3 carrier; after standing for 2-10 hours, filtering and drying the pellets, calcining at 400-600°C for 6-8 hours, and reducing with H2 at 250-450°C for 3-5 hours to obtain a catalyst.

[0007] 1) The preparation method of the platinum precursor compound M1Pt[O(SO)R1]X is as follows: ① Add Pt(PPh3)4 compound, halogen-containing potassium salt, M1, and zeolite to a benzene solution and mix them evenly; introduce inert gas protection and heat to 90-120°C for reflux reaction; after the reaction is completed, filter and remove the zeolite, add methanol to the filtrate for crystallization, filter and collect the solid, and dry to obtain [M1PtX2]n compound; the M1 is biphenyl and biphenyl derivative ligands; the X is one or more of bromine, chlorine and iodine, and is derived from a halogen-containing potassium salt, and the halogen-containing potassium salt is preferably potassium chloride and potassium iodide; n is 1 or 2; the zeolite is preferably one or more of analcime, mordenite, faujasite, and stilbite; Pt(PPh3)4, potassium The molar ratio of salt to M1 is 10:12~30:15~19; the mass ratio of the zeolite to M1 is 0.03:1~7; the volume ratio of benzene to methanol is 1:1~2; ② the toluene solution of [M1PtX2]n is mixed with the aqueous solution of -O(SO)R1 type sodium salt, stirred at 5℃~30℃ for 8~48 hours, allowed to stand, separated, and dried to obtain a platinum precursor compound of M1Pt[O(SO)R1]X type; the -O(SO)R1 group is a C1-C8 sulfinic acid group, and the molar ratio of [M1PtX2]n to -O(SO)R1 type sodium salt is 10:24~30; in the above-mentioned platinum precursor compounds [M1PtX2]n and M1Pt[O(SO)R1]X, X is the same halogen.

[0008] 2) The preparation method of the Ti-Si@Al2O3 carrier is as follows: an aluminum source, a silicon source, a titanium source and water are mixed in a mass ratio of 30:4-11:2-5:35-45 to form a suspension, an acid is added thereto, and the pH value of the solution is adjusted to 5.0-5.5 to obtain an alumina slurry, urea is added to the alumina slurry, the mixture is evenly mixed, and then the mixture is dripped into a hot oil kettle to form balls, and the balls are collected at the bottom of the kettle, and the balls are washed with water, dried, and calcined to obtain a Ti-Si@Al2O3 carrier.

[0009] In the above step 1), M1 is preferably biphenyl, and the biphenyl derivative ligand is selected from one or two of benzidine and biphenyl ether; the halogen-containing potassium salt is selected from one or more of potassium chloride, potassium bromide and potassium iodide, preferably potassium chloride and potassium iodide.

[0010] The C1-C8 sulfinic acid group is selected from sulfinates, preferably benzenesulfinate or 2-aminoethanesulfinate; more preferably one or more of sodium methanesulfinate, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2-aminoethanesulfinate.

[0011] The molar ratio of Pt(PPh3)4, potassium salt and M1 in the present invention is 10:12-30:15-25, preferably 10:12-25:15-19, which can further improve the yield of [M1PtX2]n compound and shorten the synthesis time, and the yield reaches more than 99%.

[0012] The concentration of [M1PtX2]n and the concentration of -O(SO)R1 type sodium salt are both 0.05 to 0.5 mol / L; X is preferably chlorine or iodine; and the zeolite is more preferably faujasite or stilbite.

[0013] There is no particular restriction on the mass of urea in the above preparation method, and the mass ratio of urea to aluminum source is preferably 0.1:0.5-1.7.

[0014] There is no particular restriction on the amount of benzene and methanol added in the above preparation method, and the preferred volume ratio of benzene to methanol is 1:1-2.

[0015] In the above step 2) of preparing the Ti-Si@Al2O3 carrier, the mass ratio of the aluminum source, the silicon source, the titanium source and the water is preferably 30:6-10:2-5:35-40.

[0016] The carrier prepared according to the method of the present invention can obtain Ti-Si@Al2O3 pellets of uniform size and reduce the breakage rate of the pellets. The average specific surface area of ​​the Ti-Si@Al2O3 carrier is 300-350m 2 / g, ball diameter 2.0~3.5mm, bulk density 0.40~0.55g / ml, strength ≮95N / particle. Low breakage rate, less than 0.01%.

[0017] The aluminum source includes one or more of aluminum sulfate, sodium aluminate, pseudo-boehmite, aluminum nitrate and aluminum isopropoxide. The silicon source includes one or more of silica sol, water glass, silica gel, and ethyl orthosilicate. The titanium source is one or more of titanium sol, tetrabutyl titanate, titanium tetrachloride, titanium sulfate, titanium isopropoxide, titanyl sulfate, and titanium dioxide. The acid can be one or more of nitric acid, hydrochloric acid, sulfuric acid, etc.

[0018] The molar ratio of the Sn metal salt, M1Pt[O(SO)R1]X and the alkali metal chloride is 0.5:2-7:1-10, preferably 0.5:2-5:1-6; more preferably 0.5:2-5:3-6; the Sn metal salt is one or more of stannous sulfate, tin nitrate and tin dichloride, preferably tin dichloride or tin nitrate; the alkali metal chloride is one or more of sodium chloride, potassium chloride and lithium chloride, preferably potassium chloride or lithium chloride; the volume ratio of ethanol to water in the alcohol-water solution is 0.5-5:1, preferably 2.5-3:1.

[0019] The catalyst of the present invention is prepared by controlling the pH value of the solution to be 1.0-2.5, and ensuring that the metal active components are completely adsorbed on the Ti-Si@Al2O3 carrier. The platinum precursor compound M1Pt[O(SO)R1]X is prepared and loaded on the Ti-Si@Al2O3 carrier, and the molar ratio of Pt(PPh3)4, potassium salt and M1 is 10:12-30:15-25; the mass ratio of the zeolite to M1 is 0.03:1-7; the molar ratio of [M1PtX2]n to -O(SO)R1 type sodium salt is 10:24-30; the molar ratio of Sn metal salt, M1Pt[O(SO)R1]X and alkali metal chloride is 0.5:2-7:1-10, the active sites on the catalyst exist in the form of Sn-Pt alloy, the metal Pt on the catalyst is stably immobilized, and the Pt loss rate after regeneration is low. After hydrogen reduction, the catalyst forms a PtSn active center, which is anchored on the Ti-Si@Al2O3 skeleton through a Ti-O bond, which ensures the high activity and high stability of the catalyst during the reaction and improves the low-temperature activity of the catalyst. At the same time, when the catalyst is used in the presence of trace sulfur, Ti can effectively isolate S from Pt, avoid active metal poisoning, improve the catalyst's anti-toxic performance to sulfur and other substances, and improve the stability of the catalyst in long-term use.

[0020] A process for preparing benzene by dehydrogenating cyclohexane, wherein the cyclohexane liquid space velocity is 2.0-5.0h -1 , reaction pressure 0.01-0.3MPa, hydrogen to cyclohexane volume ratio 0.01-800, reaction temperature 265-275°C. Cyclohexane conversion rate is above 99.35%, benzene yield is above 99.35%.

[0021] Compared with the prior art, the present invention has the following positive effects:

[0022] 1. A catalyst prepared by the method of the present invention. The present invention prepares a platinum precursor compound M1Pt[O(SO)R1]X and a Ti-Si@Al2O3 carrier. During the loading process according to the method of the present invention, a platinum precursor compound M1Pt[O(SO)R1]X and a Sn metal salt having a certain ratio react with the silanol groups on the Ti-Si@Al2O3 carrier and are uniformly adsorbed into the pores of the carrier, which is beneficial to improving the effective utilization rate of the unit active component of the catalyst; when calcined at 400-600° C., Pt and Sn species in the platinum precursor compound M1Pt[O(SO)R1]X react with the Ti species on the Ti-Si@Al2O3 carrier to stabilize the Pt atoms with Ti-Sn-Pt bonds; and a PtSn active center is formed under H2 reduction conditions at 250-450° C., that is, the active site on the catalyst exists in the form of a Sn-Pt alloy, the metal Pt on the catalyst is stably immobilized, and the Pt loss rate after regeneration is low. The active center is anchored on the Ti-Si@Al2O3 skeleton through the Ti-O bond. The catalyst has high activity and high stability during the reaction, especially high low-temperature activity. At the same time, when the catalyst is used in the presence of trace sulfur, Ti can effectively isolate S from Pt, avoid active metal poisoning, and improve the catalyst's anti-toxic performance to sulfur and other substances.

[0023] 2. The catalyst of the present invention is suitable for the reaction of cyclohexane dehydrogenation to benzene. Compared with industrial reaction conditions, at a lower reaction temperature (265-275°C), the cyclohexane dehydrogenation catalyst has high activity, a benzene yield of more than 99.35%, and effectively inhibits side reactions. After the catalyst reacts for a long time, there is less carbon deposition on the catalyst, and the catalyst exhibits high activity and high stability.

[0024] 3. The active sites on the catalyst prepared by the present invention can be reactivated by adopting the common regeneration method in industry. The catalyst shows high regeneration activity. The active sites on the catalyst exist in the form of Sn-Pt alloy. The metal Pt on the catalyst is stably immobilized and the Pt loss rate is low after regeneration. After regeneration, the degree of catalytic performance recovery reaches more than 99.7%, and the regeneration stability is high. Compared with the direct replacement of new catalysts after the catalysts used in current industrial devices are deactivated, the catalysts prepared by the present invention can continue to be used through regeneration, which greatly reduces the use cost of industrial device catalysts and extends the use cycle of the catalysts.

[0025] 4. The catalyst structure prepared by the present invention can effectively isolate the contact between S and Pt, so that the catalyst exhibits strong anti-toxicity and the life of the catalyst can be extended by more than 50%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the TEM image of the catalyst prepared in Example 1.

[0027] Figure 2This is a TEM image of the catalyst prepared in Example 1 after use.

[0028] Figure 3 1 is the XRD diagram of the fresh catalyst and the regenerated catalyst of Example 1.

[0029] Figure 4 This is a diagram showing the isothermal adsorption and desorption of the support and catalyst used in Example 1.

[0030] Figure 5 The pore size distribution diagram of the support and catalyst used in Example 1 is shown in FIG.

[0031] Figure 6 TG curves of Example 1, Comparative Example 1 and Comparative Example 2.

[0032] Figure 7 This is the XPS spectrum of the catalyst prepared in Example 1.

[0033] Figure 1 and Figure 2 The TEM photos of the catalyst prepared in Example 1 before and after use are shown. It can be seen from the figure that platinum particles of uniform size are dispersed on the surface of the fresh catalyst. The photo of the used catalyst is similar to that of the fresh catalyst, and no obvious aggregation between the particles is found, which is conducive to improving the effective utilization rate of the unit active component of the catalyst. This shows that the metal Pt is stably immobilized, and the catalyst has high activity and high stability during the reaction process, especially the catalyst has high low-temperature activity. Figure 3 The following are the XRD patterns of the fresh catalyst and the regenerated catalyst of Example 1. It can be clearly seen that the structure of the regenerated catalyst is basically the same as that of the fresh catalyst, indicating that the carbon deposits on the catalyst can be eliminated through the regeneration process, so that the active sites of the catalyst are exposed again. This is consistent with the high activity results of the catalyst of Example 1 after regeneration in Table 2. Figure 4 As shown, the carrier and the prepared catalyst sample of Example 1 were tested and analyzed using N2 adsorption-desorption experiments. The structure of the catalyst prepared by the method of the present invention is slightly different from that of the carrier. The platinum precursor compound prepared by the present invention reacts with the silanol groups on the carrier and is uniformly adsorbed into the pores of the carrier. After calcination at 400-600°C and H2 reduction conditions at 250-450°C, the pore structure of the carrier does not change during the catalyst preparation process (i.e., the active center formation process), indicating that the carrier structure is stable, which helps to maintain the catalyst strength and improve the stability of the catalyst during use. The pore size distribution diagram of the carrier and catalyst used in Implementation 1 is shown in FIG. Figure 5. The catalyst has a large pore size. During the catalyst preparation process, the platinum precursor compound can easily enter the pores of the carrier, react with the silanol groups on the carrier, and be uniformly adsorbed into the pores of the carrier. Through the calcination-reduction treatment, Pt migrates in the large pores and reacts with Sn to form a PtSn active center, that is, the active site on the catalyst exists in the form of Sn-Pt alloy, the metal Pt is stably immobilized on the catalyst, and the Pt loss rate is low after regeneration. The active center is anchored to the Ti-Si@Al2O3 skeleton through the Ti-O bond, without causing blockage of the catalyst pores. Figure 6 As shown, in order to explore the degree of carbon deposition on the surface of the prepared catalyst, TG characterization was used to conduct a specific analysis. The degree of carbon deposition of the catalyst is in the order of Example 1 < Comparative Example 1 < Comparative Example 2. It can also be seen from the dehydrogenation evaluation data that the benzene yield of the catalyst in Comparative Example 1 is at a disadvantage, which also corresponds to its higher degree of carbon deposition, indicating that the side reactions of the catalyst are more serious, making it easy for coke to block the pores and cause it to deactivate. However, the active center of the catalyst in Example 1 has a weak adsorption effect on the benzene generated by the reaction, which promotes the desorption of benzene molecules, thereby reducing the formation of carbon deposition. According to the evaluation data, the catalyst in Example 1 has the best catalytic performance. Figure 7 The XPS graph related to the 4f electronic state of platinum is shown, indicating that the platinum atom is in the metallic state Pt(0). In addition, compared with the single metal platinum reference value (71.0eV), the platinum 4f peak moves to a lower binding energy (70.5eV), which is due to the formation of PtSn active centers by Pt and Sn (i.e., the active sites on the catalyst exist in the form of Sn-Pt alloy), resulting in a small amount of electrons transferred from Sn to Pt, increasing the local electron density and local Coulomb repulsion on Pt, thereby reducing the binding energy of its electrons. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] Example 1

[0036] 1) Preparation of platinum precursor compound: ① Add 5.60 g of tetrakis(triphenylphosphine)platinum (Pt content 15.2%), 0.49 g of potassium chloride, 1.14 g of biphenyl, and 0.02 g of faujasite to 100 mL of benzene solution, and stir to mix evenly; introduce N2 protection, heat to 95°C for reflux reaction; after the reaction is completed, filter, add 150 mL of methanol to the filtrate, the volume ratio of benzene to methanol is 1:1, filter and collect the solid, and dry to obtain C 12 H 10 PtCl2 compound; the molar ratio of Pt(PPh3)4, potassium chloride and biphenyl is 10:15:17; ② 0.06 mol / L C 12 H 1050 mL of PtCl2 toluene solution was mixed with 130 mL of 0.06 mol / L sodium benzenesulfinate aqueous solution, stirred at 10 °C for 24 hours, allowed to stand, separated, and dried to obtain C 12 H 10 Pt[O(SO)C6H5]Cl compound. 12 H 10 The molar ratio of PtCl2 to sodium benzenesulfinate is 10:26;

[0037] 2) Preparation of Ti-Si@Al2O3 carrier: 120g aluminum isopropoxide, 18g tetraethyl orthosilicate, 12g titanium sulfate and 160g water were mixed to prepare a suspension, nitric acid was added thereto, and the pH value of the solution was adjusted to 5.0, and the solution obtained an alumina slurry. 20g urea was added to the alumina slurry, mixed evenly, and then dripped into a hot oil kettle to form balls. The balls were collected at the bottom of the kettle, washed with water, dried, and calcined to obtain a Ti-Si@Al2O3 carrier. The mass ratio of aluminum isopropoxide, tetraethyl orthosilicate, titanium sulfate and water was 30:4.5:3:40; the mass ratio of urea to aluminum source was 0.1:0.6;

[0038] 3) Preparation of catalyst: 0.012g tin dichloride, 0.164g C 12 H 10 Pt[O(SO)C6H5]Cl and 0.011g lithium chloride were added to a mixed solution of 8mL ethanol and 3mL water, and the pH value of the solution was adjusted to 2.0; the above solution was impregnated onto the Ti-Si@Al2O3 carrier; after standing for 6 hours, the pellets were filtered, dried, calcined at 560℃ for 6 hours, and reduced with H2 at 280℃ for 5 hours to obtain the catalyst. Tin dichloride, C 12 H 10 The molar ratio of Pt[O(SO)C6H5]Cl to lithium chloride is 0.5:3:2.5. Catalyst composition: by mass, the platinum content is 0.35wt% of the catalyst mass, the alkali metal content is 0.01wt% of the catalyst mass, and the tin content is 0.035wt% of the catalyst mass.

[0039] Example 2

[0040] The preparation of platinum precursor compounds, the preparation of Ti-Si@Al2O3 carriers, and the preparation of catalysts were prepared according to the steps of Example 1, and the halogen-containing potassium salt was adjusted to potassium iodide, M1 was diphenyl ether, the mass ratio of zeolite to M1 was 0.03:2, the -O(SO)R1 group was sodium p-toluenesulfinate, the volume ratio of benzene to methanol was 1:1, the molar ratio of [M1PtX2]n to sodium p-toluenesulfinate was 10:29; the mass ratio of aluminum source, silicon source, titanium source and water was 30:7:3:37, the mass ratio of urea to aluminum source was 0.1:0.7; the molar ratio of Pt(PPh3)4, potassium salt and M1 was 10:23:18. The molar ratio of stannous sulfate, M1Pt[O(SO)R1]X, and potassium chloride was 0.5:5:6. The volume ratio of ethanol to water in the alcohol aqueous solution is 1:1. The catalyst composition is as follows: by mass, the platinum content is 0.35wt% of the catalyst mass, the alkali metal content is 0.084wt% of the catalyst mass, and the tin content is 0.02wt% of the catalyst mass.

[0041] Example 3

[0042] The preparation of platinum precursor compounds, the preparation of Ti-Si@Al2O3 carriers, and the preparation of catalysts were prepared according to the steps of Example 1, and the halogen-containing potassium salt was adjusted to potassium bromide, M1 was benzidine, the -O(SO)R1 group was sodium methanesulfinate, the mass ratio of zeolite to M1 was 0.03:3, the molar ratio of [M1PtX2]n to sodium methanesulfinate was 10:28; the mass ratio of aluminum source, silicon source, titanium source and water was 30:9:5:40; the mass ratio of urea to aluminum source was 0.1:1.1; the molar ratio of Pt(PPh3)4, potassium salt and M1 was 10:20:16. The molar ratio of Sn metal salt, M1Pt[O(SO)R1]X, and sodium chloride was 0.5:3:5. The volume ratio of ethanol to water in the alcohol aqueous solution is 3:1. The catalyst composition is as follows: by mass, the platinum content is 0.35wt% of the catalyst mass, the alkali metal content is 0.069wt% of the catalyst mass, and the tin content is 0.036wt% of the catalyst mass.

[0043] Example 4

[0044] Preparation of platinum precursor compound, preparation of Ti-Si@Al2O3 carrier, and preparation of catalyst are prepared according to the steps of Example 1, adjusting the halogen-containing potassium salt to potassium iodide, M1 to biphenyl ether, -O(SO)R1 group to sodium 2-aminoethanesulfinate, the mass ratio of zeolite to M1 to 0.03:2, the molar ratio of [M1PtX2]n to sodium 2-aminoethanesulfinate to 10:26; the mass ratio of aluminum source, silicon source, titanium source and water is preferably 30:8:3:35, and the mass ratio of urea to aluminum source is 0.1:0.85; the molar ratio of Pt(PPh3)4, potassium salt and M1 is 10:17:19. The molar ratio of Sn metal salt, M1Pt[O(SO)R1]X and lithium chloride is 0.5:6:3. The volume ratio of ethanol to water in the alcohol aqueous solution is 2:1. Catalyst composition: by mass, the platinum content is 0.35wt% of the catalyst mass, the alkali metal content is 0.006wt% of the catalyst mass, and the tin content is 0.018wt% of the catalyst mass.

[0045] Example 5

[0046] The preparation of platinum precursor compound, the preparation of Ti-Si@Al2O3 carrier and the preparation method of catalyst are prepared according to the steps of Example 1, the halogen-containing potassium salt is adjusted to potassium iodide, M1 is diphenyl ether, the mass ratio of zeolite to M1 is 0.03:5, the -O(SO)R1 group is sodium benzenesulfinate, the molar ratio of [M1PtX2]n to sodium benzenesulfinate is 10:26; the mass ratio of aluminum source, silicon source, titanium source and water is preferably 30:6:4:35, the mass ratio of urea to aluminum source is 0.1:1.4; the molar ratio of Pt(PPh3)4, potassium salt and M1 is 10:12:20; the molar ratio of Pt(PPh3)4. Tin nitrate, M1Pt[O(SO)R1]X and lithium chloride is 0.5:4:5. Catalyst composition: by mass, the platinum content is 0.35wt% of the catalyst mass, the alkali metal content is 0.016wt% of the catalyst mass, and the tin content is 0.027wt% of the catalyst mass.

[0047] Comparative Example 1

[0048] The carrier of Example 1 was used as the carrier, and the same amount of tin dichloride, chloroplatinic acid, lithium chloride and other components were loaded, but not added in the form of the precursor of the present invention. The other steps and contents were the same as those of Example 1, and a comparative catalyst 1 was obtained.

[0049] Comparative Example 2

[0050] The carrier of Example 1 was used as the carrier, except that the catalyst preparation process was calcined at 800° C. for 4 h. The other steps and contents were the same as those of Example 1, to obtain a comparative catalyst 2.

[0051] Comparative Example 3

[0052] The carrier of Example 1 was used as the carrier, the only difference being that the molar ratio of Pt(PPh3)4, potassium chloride and biphenyl was 10:45:17, and comparative catalyst 3 was obtained.

[0053] Comparative Example 4

[0054] The carrier of Example 1 is used as the carrier, the only difference is that tin dichloride, C 12 H 10 The molar ratio of Pt[O(SO)C6H5]Cl and lithium chloride is 0.01:3:2.5.

[0055] Comparative Example 5

[0056] The carrier of Example 1 was used as the carrier, the only difference being that the pH value of the catalyst preparation process was 4, and the other steps and contents were the same as those of Example 1, to obtain a comparative catalyst 5.

[0057] Comparative Example 6

[0058] The carrier was prepared according to the steps of Example 1, except that no titanium salt was added. The other steps and contents were the same as those of Example 1, and a comparative catalyst 6 was obtained.

[0059] 1. Cyclohexane dehydrogenation test

[0060] The catalysts obtained in Examples 1-5 and the catalyst obtained in Comparative Example 1 were subjected to cyclohexane dehydrogenation tests using a fixed bed evaluation method. The control parameters in the process flow used are as follows: cyclohexane liquid space velocity is 5.0 h -1 , reaction pressure 0.02MPa, volume ratio of hydrogen to cyclohexane 0.01, reaction temperature 270°C; sampling was taken after 200h of reaction, and the results are shown in Table 1.

[0061] Table 1 Cyclohexane dehydrogenation performance

[0062]

[0063] As can be seen from Table 1, in the catalyst prepared according to the method of the present invention, during the loading process, the platinum precursor compound M1Pt[O(SO)R1]X and the Sn metal salt with a certain ratio react with the silanol groups on the Ti-Si@Al2O3 carrier and are uniformly adsorbed into the pores of the carrier, which is beneficial to improving the effective utilization rate of the catalyst unit active component; when calcined at 400-600°C, the Pt and Sn species in the platinum precursor compound M1Pt[O(SO)R1]X react with the Ti species on the Ti-Si@Al2O3 carrier to stabilize the Pt atoms with the Ti-Sn-Pt bond; under the H2 reduction condition at 250-450°C, a PtSn active center is formed, that is, the active site on the catalyst exists in the form of Sn-Pt alloy, the metal Pt on the catalyst is stably immobilized, and the Pt loss rate after regeneration is low. The active center is anchored on the Ti-Si@Al2O3 skeleton through the Ti-O bond. The catalyst prepared by the method of the present invention has stable metal Pt immobilization and high activity during the reaction process. In particular, at a relatively low reaction temperature (270° C.), the cyclohexane dehydrogenation catalyst can exhibit high activity, with a benzene yield greater than 99.35%, and effectively inhibiting side reactions.

[0064] 2. Catalyst regeneration stability test

[0065] When the catalyst is regenerated after deactivation, N2 is first introduced from the reactor inlet to completely blow out the residual solution in the bed, and then the bed catalyst is regenerated. After N2 is introduced and treated at 150°C for 3 hours, it is treated at 80°C for 3 hours under hydrogen conditions. The performance results after catalyst regeneration are shown in Table 2. After the catalyst prepared by the present invention is deactivated and subjected to simple regeneration treatment, the benzene yield of Example 1 is maintained at 99.05%, and the degree of catalytic performance recovery reaches 99.7% compared with the fresh catalyst; while the benzene yield of the catalyst in Comparative Example 1 after regeneration is 71.48%, and the degree of catalytic performance recovery is 80.0% compared with the fresh agent, which is much lower than the present invention. This shows that the active sites on the catalyst prepared by the present invention, that is, the active sites on the catalyst exist in the form of Sn-Pt alloy, the metal Pt on the catalyst is stably immobilized, and the Pt loss rate after regeneration is low. The secondary activation can be achieved by adopting the regeneration method commonly used in industry, and the catalyst shows high regeneration stability.

[0066] According to the results of the economic operation of industrial equipment, the catalyst has to have a regeneration recovery rate of more than 95.18% after deactivation to be worth regenerating. This shows that the catalyst prepared by the present invention can greatly reduce the use cost of the catalyst in the industrial equipment and extend the service life of the catalyst. In addition, by measuring the Pt content on the catalyst after regeneration, it can be seen that the catalyst prepared by the present invention, such as Example 1, has a loss rate of precious metal content of 2.9% after regeneration, while the Pt content loss rates of the catalysts of Comparative Example 1 and Comparative Example 4 after regeneration are 11.5% and 14.3%, respectively, which are much higher than those of the present invention. This shows that the active sites on the catalyst of the present invention exist in the form of Sn-Pt alloy, which makes the Pt metal immobilization stable and the Pt loss rate low.

[0067] Table 2 Catalyst regeneration stability

[0068]

[0069] 3. Catalyst anti-poisoning stability test

[0070] The catalysts obtained in Examples 1-5 and the catalysts obtained in Comparative Examples 1 and 6 were subjected to anti-poisoning tests using a fixed bed method. The control parameters in the process flow used are as follows: cyclohexane liquid space velocity is 5.0 h -1 , reaction pressure 0.02MPa, hydrogen to cyclohexane volume ratio 0.01, carbon disulfide content in cyclohexane 0.5ppm, reaction temperature 270°C; sampling after 24h reaction, the catalyst performance results are shown in Table 3:

[0071] Table 3 Catalyst anti-poisoning stability

[0072]

[0073]

[0074] As is known to all, precious metal catalysts have strict requirements on the impurity content in raw materials, and trace amounts of toxic substances (such as sulfur, chlorine, etc.) can cause catalyst poisoning. In actual production, especially some production enterprises involving the use of precious metal catalysts, improper operation can lead to catalyst poisoning, greatly increase production costs, and lose market competitiveness of products. Therefore, how to improve the anti-toxicity of the catalyst and give full play to the activity of the catalyst is an important problem to be solved in the catalyst design and development process. As can be seen from Table 3, after the anti-toxicity experiment, the benzene yield of the embodiment catalyst prepared by the present invention is still maintained at more than 99%, and the benzene yield is reduced by 0.35%-0.4% compared with the benzene yield obtained under sulfur-free conditions. The benzene yield of the catalyst in Comparative Example 1 decreased by about 5.77%. This shows that after the catalyst in Comparative Example 1 contacts a large amount of sulfur-containing substances, the catalyst is rapidly deactivated. In the embodiment catalyst prepared by the present invention, under the condition of trace sulfur, Ti can effectively isolate S from contact with Pt, can avoid active metal poisoning, and improve the anti-toxicity of the catalyst to sulfur and other substances. The benzene yield of the catalyst in Comparative Example 6 decreased by about 3.95%. This also further confirms that the interaction between titanium and the active component has a positive effect on maintaining high anti-toxicity of the catalyst, which is consistent with the results of Examples 1-5.

[0075] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A catalyst for dehydrogenating cyclohexane to produce benzene, characterized in that: The catalyst composition is as follows: Ti-Si@Al2O3 is used as a carrier, platinum, tin and alkali metals are used as active components, and the active sites on the catalyst exist in the form of Sn-Pt alloy. The platinum content of the active component is 0.3-1.5wt% of the catalyst mass, preferably 0.3-1.0wt%, and more preferably 0.3-0.8wt% by mass; the alkali metal content is 0.005-0.4wt% of the catalyst mass, and the tin content is 0.01-0.2wt% of the catalyst mass; the titanium oxide of the Ti-Si@Al2O3 carrier accounts for 0.02-8% of the carrier mass, and the silicon oxide accounts for 0.1-15% of the carrier mass.

2. A catalyst for dehydrogenating cyclohexane to produce benzene according to claim 1, characterized in that: The average specific surface area of ​​the Ti-Si@Al2O3 carrier is 300-350m 2 / g, ball diameter 2.0~3.5mm, bulk density 0.40~0.55g / ml, strength ≮95N / particle.

3. A method for preparing the catalyst for dehydrogenation of cyclohexane to benzene according to claim 1 or 2, characterized in that: The invention comprises the following steps: adding Sn metal salt, platinum precursor compound M1Pt[O(SO)R1]X and alkali metal chloride into an alcohol aqueous solution, adjusting the solution pH value to 1.0-2.5, wherein the molar ratio of the Sn metal salt, M1Pt[O(SO)R1]X and alkali metal chloride is 0.5:2-7:1-10, preferably 0.5:2-5:1-6; more preferably 0.5:1-5:3-6, to obtain an impregnation solution; impregnating the obtained impregnation solution onto a Ti-Si@Al2O3 carrier; after standing for 2-10 hours, filtering and drying the pellets, calcining at 400-600°C for 6-8 hours, and reducing with H2 at 250-450°C for 3-5 hours, to obtain a catalyst.

4. The method for preparing the catalyst according to claim 3, characterized in that: The preparation method of the platinum precursor compound M1Pt[O(SO)R1]X comprises the following steps: ① adding a Pt(PPh3)4 compound, a halogen-containing potassium salt, M1 and a zeolite to a benzene solution and mixing them evenly; introducing an inert gas for protection and heating to 90-120°C for reflux reaction; after the reaction is completed, filtering to remove the zeolite, adding methanol to the filtrate for crystallization, filtering to collect the solid, and drying to obtain a [M1PtX2]n compound; wherein M1 is a biphenyl and a biphenyl derivative ligand; wherein X is one or more of bromine, chlorine and iodine, and is derived from a halogen-containing potassium salt, and the halogen-containing potassium salt is preferably potassium chloride and potassium iodide; n is 1 or 2, and Pt(PPh3 )4. The molar ratio of potassium salt to M1 is 10:12~30:15~19; ② Mix the toluene solution of [M1PtX2]n with the aqueous solution of -O(SO)R1 type sodium salt, stir at 5℃~30℃ for 8~48 hours, let stand, separate, and dry to obtain a platinum precursor compound of M1Pt[O(SO)R1]X type; the -O(SO)R1 group is a C1-C8 sulfinic acid group, and the molar ratio of [M1PtX2]n to -O(SO)R1 type sodium salt is 10:24~30; in the above-mentioned platinum precursor compounds [M1PtX2]n and M1Pt[O(SO)R1]X, X is the same halogen.

5. The method for preparing the catalyst according to claim 3, characterized in that: The mass ratio of the zeolite to M1 is 0.03:1-7; the zeolite is preferably one or more of analcime, mordenite, faujasite, and stilbite; and the volume ratio of benzene to methanol is 1:1-2.

6. The method for preparing the catalyst according to claim 3, characterized in that: The preparation method of the Ti-Si@Al2O3 carrier comprises the following steps: mixing an aluminum source, a silicon source, a titanium source and water to form a suspension, wherein the mass ratio of the aluminum source, the silicon source, the titanium source and the water is 30:4-11:2-5:35-45, preferably 30:6-10:2-5:35-40, adding acid thereto, adjusting the pH value of the solution to 5.0-5.5, obtaining an alumina slurry, adding urea to the alumina slurry, mixing evenly, and then dripping the mixture into a hot oil kettle to form balls, collecting the balls at the bottom of the kettle, washing, drying and roasting the balls to obtain the Ti-Si@Al2O3 carrier; the mass ratio of urea to the aluminum source is 0.1:0.5-1.

7.

7. The method for preparing the catalyst according to claim 4, characterized in that: The C1-C8 sulfinic acid group is selected from sulfinates, preferably benzenesulfinate or 2-aminoethanesulfinate; more preferably one or more of sodium methanesulfinate, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2-aminoethanesulfinate.

8. The method for preparing the catalyst according to claim 4, characterized in that: The molar ratio of Pt(PPh3)4, potassium salt and M1 is 10:12-25:15-19.

9. The method for preparing the catalyst according to claim 4, characterized in that: The biphenyl derivative ligand is selected from one or two of benzidine and biphenyl ether.

10. Use of the catalyst for cyclohexane dehydrogenation according to any one of claims 1 to 2 in cyclohexane dehydrogenation to benzene, characterized in that: The cyclohexane liquid space velocity is 2.0-5.0h -1 , reaction pressure 0.01-0.3MPa, volume ratio of hydrogen to cyclohexane 0.01-800, reaction temperature 265-275°C.

Citation Information

Patent Citations

  • Dehydrogenation catalyst, preparation method and application thereof, and method for preparing benzene ring through cyclohexane dehydrogenation

    CN115445612A

  • Low-temperature dehydrogenation catalyst and preparation method thereof

    CN115703062A

  • Catalyst for preparing aromatic hydrocarbon by dehydrogenation of six-membered cycloalkane and preparation method thereof

    CN115999591A